The price you pay - Petrie, Nicholas (Petrie, Nicholas. Peter Ash novel, 2024)
"Peter Ash must follow his closest friend, Lewis, into the criminal underworld when secrets from the past threaten everything they hold dear in this propulsive new thriller from the bestselling and award-winning series"--